Anomaly of origin of the coronary arteries. Single coronary artery in a patient with symptoms of myocardial ischemia - Vilaú Jiménez, Mailyn; Victores Chacón, Rasiel; Llerena Rojas, Luis Roberto; Martinez Gonzalez, Aniley; Junco Labrador, Liyanis (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Congenital alterations of the coronary arteries are rare anomalies. The single coronary artery with origin in the right sinus of Valsalva is even more infrequent, but it is of great importance because it can begin with mild to potentially fatal ischemic phenomena or lead to sudden cardiac death. The following case is a 54-year-old patient, who came to the clinic with oppressive precordial pain, both at rest and during physical exertion. A myocardial perfusion study was performed using the ischemia detection protocol, showing signs of ischemia in the territory of the anterior descending artery, a coronary angiography was performed where a dominant right coronary artery without atherosclerotic lesions was observed, and the left coronary sinus was not found. The diagnosis was made from a coronary angio-CT scan where a single coronary artery originating from the right coronary sinus was observed.